Churces and Prophecies in the Mythological Spanish Baroque Theatre (1597-1674) (Castilla. Estudios de Literatura, 2016)
In thi paper, we study the dramatic function of temples and prophecies on the mythological Spanish Baroque theater, from a comparative perspective. In a limited corpus of Feliex Lope de Vega y Pedro Calderon de la Barca, the interpretation of this elements reveal in thematic, spatial and theatrical levels, interesting convergences and divergences.
Keywords: theatre; Gold century; mythology; Lope de Vega; Calderón de la Barca; prophecies